Analysis of QTLs Associated with the Rice Quality Related Gene by Double Haploid Populations - Gyu-Ho Lee; Byung-Wook Yun; Kyung-Min Kim (International Journal of Genomics)
We investigated the growth characteristics and analyzed the physicochemical properties of a doubled haploid population derived from a cross between “Cheongcheong” and “Nagdong” to breed a rice variety that tastes good after cooking and to detect quantitative trait loci (QTLs) associated with the taste of cooked rice. The results showed that these compounds also represent a normal distribution. Correlation analysis of the amylose, protein, and lipid contents indicated that each compound is related to the taste of cooked rice. The QTLs related to amylose content were 4 QTLs, protein content was 2 QTLs, and lipid content was 2 QTLs. Four of the QTLs associated with amylose content were detected on chromosomes 7 and 11. The index of coincidence for the QTLs related to amylose, protein, and lipid content was 70%, respectively. These markers showing high percentage of coincidence can be useful to select desirable lines for rice breeding.